Economic Restructuring, Unemployment, and Growth in a Transition Economy - Krajnyak, Kornelia (IMF Working Papers; Working Paper, 1993)
This paper develops a model of the process of reallocation of labor from the state sector to the private sector. When growth is exogenously determined, we show that in the initial stages of transition unemployment will rise over time. After a critical stage in the transition process, restructuring is accompanied by a decline in unemployment. When growth is endogenously determined, and human capital is acquired by learning-by-doing, we show that whether restructuring eventually occurs is determined by the level of human capital in the private sector and the rate of unemployment. The effects of various shocks and government policies in affecting the costs, speed, and eventual outcome of restructuring are analyzed.